SISTEM INFORMASI PRAKERIN BERBASIS WEB PADA SMKN 1 ANYER - Dedi Juniansha; Korneilis Korneilis (LPPM Unbaja, 2020)
Information system Praktek Kerja Industri in smkn 1 anyer, Strata I Program Informatics Engineering, College Information Management and Computer Cilegon, Praktek Kerja Industri information system is an information system that provides information to students to perform industrial work as a condition of graduation later, the method used is the method of observation, Interviews, and literature. Support software study method in making this application phpmyadmin, komodo editor, mysql has been able to create a Praktek Kerja Industri information system in smkn 1 anyer.